Knowledge Management Strategy, Innovation, and Performance in Small Business Enterprise in Indonesia - Aryo Bismo; Wensin Halim; Monica Andini Erwinta (The Winners, 2021)
The research aimed to provide view about the knowledge management strategies that specifically testing both codification and personalization, and their consequences on innovation and performance in small business enterprise. Data were collected from 46 small business enterprises in Indonesia through online questionnaires, and were analysed using structural equation modelling. The results reveal that knowledge management strategies—codification and personalization—have impacts on innovation and performances directly and indirectly through the increase on innovation capability. It is considered that the research will help small business enterprises to establish a good knowledge management strategy to obtain better profit on a specific condition and environment.